2018
DOI: 10.1186/s12969-018-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective parents and permissive children: what qualitative interviews with parents and children can tell us about the feasibility of juvenile idiopathic arthritis trials

Abstract: BackgroundPatient recruitment can be very challenging in paediatric studies, especially in relatively uncommon conditions, such as juvenile idiopathic arthritis (JIA). However, involving children and young people (CYP) in the design of such trials could promise a more rapid trajectory towards making evidence-based treatments available. Studies involving CYP are advocated in the literature but we are not aware of any early stage feasibility studies that have qualitatively accessed the perspectives of parents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…56 This multiperspective approach offers a comprehensive approach to identifying barriers to and facilitators of recruitment, to enhancing families' experience of the process and to informing future trial design. 59 In this section, we examine the effect of recruitment training (informed by the communication study findings) on health professionals' CONTRACT consultations with families and discuss the strengths and weaknesses of the communication study. We offer recommendations (see Appendix 2) to inform a future definitive trial to compare non-operative treatment with appendicectomy, and discuss the broader implications of the findings for the design and conduct of surgical versus non-surgical trials, paediatric trials and research conducted in an acute setting.…”
Section: Discussionmentioning
confidence: 99%
“…56 This multiperspective approach offers a comprehensive approach to identifying barriers to and facilitators of recruitment, to enhancing families' experience of the process and to informing future trial design. 59 In this section, we examine the effect of recruitment training (informed by the communication study findings) on health professionals' CONTRACT consultations with families and discuss the strengths and weaknesses of the communication study. We offer recommendations (see Appendix 2) to inform a future definitive trial to compare non-operative treatment with appendicectomy, and discuss the broader implications of the findings for the design and conduct of surgical versus non-surgical trials, paediatric trials and research conducted in an acute setting.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, any clinical trial involving treatment requires careful and rigorous development with meaningful input from CYP and their families from the outset, to mitigate against challenges in the delivery of the clinical trial itself. 125 The survey that was conducted after the consensus meeting was completed by 45 HCPs and 16 CYP and their families. This allowed a wider group of individuals to provide their opinion in the choice of outcomes that should be used in any future trial.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent discussions were then useful in clarifying the 10 outcome measures that had previously been selected for potential inclusion in a feasibility study, helping to eliminate misunderstanding, particularly among non-HCPs. 119 To add additional context to the SIRJIA consensus meeting, participants were given a short presentation that highlighted the results from the preceding qualitative study that explored families' views on outcomes of importance to them in receiving CS treatment for JIA, 125 as part of the larger SIRJIA study. 36 Stage 4: group-based discussion (health-care professionals alongside children and young people with families) of the results of the first voting exercise and the inclusion/exclusion criteria for the prospective feasibility study…”
Section: Stage 3: First Voting Exercise Of Primary Outcome Measuresmentioning
confidence: 99%
“…Glucocorticoid medications offer potential for rapid clinical improvement, but frequently lead to side effects that adversely impact HRQOL. Many studies looking at the patient experience within paediatric rheumatic diseases, have found the burden of glucocorticoid treatment to be a recurring theme [ 14 17 ]. These range from short-term effects that may go unrecognised by clinicians (e.g., weight gain, anxiety, skin changes and poor sleep) to long-lasting adverse events (e.g., delayed growth and puberty, diabetes, loss of bone mass and fractures) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%